Neighbourhood Regeneration in Istanbul – from Earthquake Mitigation to Planned Displacement and Gentrification - Gibson, Mike; Gökşin, Zeynep Ayşe (International Planning History Society Proceedings, 2016)
The paper analyses the development of neighbourhood regeneration in Istanbul since the 1999 Marmara earthquake, contrasting initial concepts and policy recommendations with actual policies and outcomes. It draws on original research to develop an analytical framework which focuses on the evolving inter-relationship between academic and professional discourses, innovative neighbourhood projects and central government’s neo-liberal economic and political strategies. The analysis identifies three phases. The first was the initial response to the 1999 earthquake, in the context of recovery from the 2001 recession, the early EU harmonisation process and the advent of single party (Justice and Development Party-AKP) government. This focussed attention on the legacy of the unregulated growth of Istanbul in the second half of the 20th century – thousands of poorly constructed earthquake vulnerable apartment blocks. The metropolitan municipality commissioned studies from local universities and international experts. Combined with an EU funded pilot project, this innovative research established the key components of a Turkish model of strategic earthquake resilient redevelopment of poor neighbourhoods, with minimum gentrification. But in the context of a rapidly growing economy, faltering EU harmonization and a second term for an increasingly pro-development government the second phase was dominated by the controversial implementation of the 2005 renewal law No. 5366 in the city’s historic districts. The central government housing development agency TOKI became the leading actor, working in partnership with district municipalities. Implementation was epitomized by the Sulukule Project which destroyed the Roma community. In parallel, the Fener-Balat EU project was succeeded by a construction company-led project which promoted gentrification. There was growing collective resistance from residents to regeneration projects in gecekondu (squatter) neighbourhoods. The concept of neighbourhood regeneration as earthquake mitigation was marginalized - gentrification was seen as a greater threat. A third term AKP administration prioritised supporting the construction sector to sustain economic development in the aftermath of the global downturn, but it also had to respond to the 2011 Van earthquake. The third phase began with the 2012 urban regeneration law No. 6306 which aimed to stimulate neighbourhood regeneration outside historic districts. Forty Urban Regeneration Areas have been designated in fifteen districts, through processes controlled by central government. However these neighbourhoods are generally not those most vulnerable to earthquake destruction, but those where redevelopment is highly profitable. A case study of Bağcılar illustrates the limitations of contemporary practice but also identifies positive developments which could be built on under changed circumstances. The paper concludes that the 20th century solutions to the challenges of urbanisation have substantially defined the neighbourhood regeneration problems of the 21st century and that current ‘top-down’ neo-liberal urban policies will not protect the poor from future earthquakes. Two parallel tasks are proposed for progressive academics and professionals: ‘bottom-up’ empirical research to provide hard evidence of the socially regressive outcomes of current practice and its failure to deliver earthquake resilience; and the definition of alternative models of neighbourhood regeneration, together with a specification of the changes in national policies necessary to deliver them.